Dielectric composition and electronic component

Through dielectric compositions dominated by strontium and tantalum, the use of titanium, niobium, alkali metals and lead is avoided, and specific chemical composition and process conditions are adopted to solve the problem of lowering relative dielectric constant and resistivity of the dielectric over a wide temperature range. It achieves high density and low dielectric loss effects, meeting environmental friendliness and stability requirements.

CN114823135BActive Publication Date: 2024-12-17TDK CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111542550.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-01-20
Filing Date
2021-12-16
Publication Date
2024-12-17
Estimated Expiration
2041-12-16

AI Technical Summary

Technical Problem

The existing dielectric compositions are difficult to display high relative dielectric constants over a wide temperature range, and are prone to oxygen defects, resulting in reduced resistivity and increased dielectric loss, and contain limited titanium, niobium and alkali metals, affecting composition stability. and environmentally friendly.

Method used

The dielectric composition using strontium and tantalum as the main components is avoided by the chemical composition of {BaxSr(1-x)}mTa4O12, and the use of titanium, niobium, alkali metal and lead is used, and the preferred sintering temperature and process conditions are used to form high density. Dielectrics with high relative dielectric constant and low dielectric loss.

Benefits of technology

Maintain high relative dielectric constant and resistivity over a wide temperature range, reduce dielectric loss, avoid oxygen defects and composition deviations, meet X8S characteristics, and comply with RoHS standards, and are environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114823135B_ABST
    Figure CN114823135B_ABST
Patent Text Reader

Abstract

The present invention provides a dielectric composition having a high relative dielectric constant in a wide temperature range. The dielectric composition of the present invention contains strontium and tantalum as main components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a dielectric composition and an electronic component. Background Art

[0002] In recent years, a dielectric composition showing a high relative dielectric constant over a wide temperature range has been required for electronic components for automotive use and the like. Summary of the invention

[0003] Problems to be solved by the invention

[0004] The present invention has been developed in view of such actual circumstances, and an object of the present invention is to provide a novel dielectric composition having a high relative dielectric constant over a wide temperature range.

[0005] Technical solutions to solve problems

[0006] The dielectric composition of the present invention contains strontium and tantalum as main components.

[0007] According to the dielectric composition of the present invention, it is possible to exhibit a high relative dielectric constant in a wide temperature range.

[0008] Preferably, barium is further contained as a main component.

[0009] Preferably, the dielectric composition of the present invention contains substantially no titanium, niobium, alkali metals, and lead.

[0010] As dielectric compositions showing a high relative dielectric constant, there can be mentioned BaTiO3 containing titanium (Ti) as the main component, (Sr, Ba)Nb2O6 containing niobium (Nb) as the main component, (Na, K)NbO3 containing alkali metals, and Pb(Zr, Ti)O3 containing Pb.

[0011] The dielectric composition of the present invention does not actually contain titanium and niobium, so it is not easy to produce oxygen defects. In other words, the change of valence state is suppressed. Therefore, because sintering is carried out simultaneously with the base metal, it is believed that even if reduction sintering is carried out, the valence state is not easy to change, and the reduction of resistivity is suppressed, and high resistivity can be displayed in a wide temperature range. In addition, based on the same reason, it is believed that low dielectric loss can be displayed.

[0012] Furthermore, since the dielectric composition of the present invention contains substantially no alkali metal, it is possible to prevent compositional variation of the dielectric composition and furnace contamination due to evaporation of the alkali metal.

[0013] In addition, although the use of lead is restricted by RoHS (Restriction of Hazardous Substances Directive) and the like, the dielectric composition of the present invention does not substantially contain lead.

[0014] Preferably, the main component is composed of {Ba x Sr (1-x)} m Ta4O 12 This indicates that x is 0.75 or less. As a result, the relative dielectric constant becomes higher, the density and resistivity become higher, and the dielectric loss becomes lower.

[0015] More preferably, x is 0.1 to 0.75, whereby the relative dielectric constant becomes higher.

[0016] Preferably, m is 1.9 to 2.1. This makes it possible to increase the relative dielectric constant, increase the density and the resistivity, and reduce the dielectric loss.

[0017] Preferably, the crystal system of the main component crystal is tetragonal system.

[0018] Furthermore, the electronic component of the present invention comprises the above-mentioned dielectric composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic cross-sectional view of a multilayer ceramic capacitor according to one embodiment of the present invention.

[0020] Figure 2 This is a schematic cross-sectional view of a thin film capacitor according to one embodiment of the present invention.

[0021] Figure 3 This is a graph showing the relationship between the measurement temperature and the relative dielectric constant of sample numbers 1 to 5.

[0022] Figure 4 This is a graph showing the relationship between the density of a dielectric composition and the relative dielectric constant.

[0023] Figure 5 This is a graph showing the relationship between the density of the dielectric composition and the dielectric loss.

[0024] Figure 6 This is a graph showing the relationship between the density and resistivity of a dielectric composition. DETAILED DESCRIPTION

[0025] [ First embodiment ]

[0026] < Multilayer Ceramic Capacitors >

[0027] A multilayer ceramic capacitor 1 as an example of an electronic component of the present embodiment is Figure 1. The laminated ceramic capacitor 1 has a component body 10 having a structure in which dielectric layers 2 and internal electrode layers 3 are alternately stacked. A pair of external electrodes 4 are formed at both ends of the component body 10, which are respectively connected to the internal electrode layers 3 alternately arranged inside the component body 10. The shape of the component body 10 is not particularly limited, but is generally a rectangular parallelepiped. In addition, the size of the component body 10 is not particularly limited, as long as it is set to an appropriate size according to the application.

[0028] < Dielectric layer >

[0029] The dielectric layer 2 is composed of a dielectric composition of this embodiment described later.

[0030] The thickness of each dielectric layer 2 (interlayer thickness) is not particularly limited and can be set according to desired characteristics and applications, etc. Generally, the interlayer thickness is preferably 30 μm or less, more preferably 15 μm or less, and further preferably 10 μm or less.

[0031] < Internal electrode layer >

[0032] In the present embodiment, the internal electrode layers 3 are stacked so that the respective end portions are alternately exposed on the surfaces of two opposing end faces of the element body 10 .

[0033] There is no particular limitation on the conductive material contained in the internal electrode layer 3. Examples of precious metals used as conductive materials include palladium (Pd), platinum (Pt), and silver (Ag)-Pd alloys. Examples of base metals used as conductive materials include nickel (Ni), Ni-based alloys, copper (Cu), and Cu-based alloys. In addition, Ni, Ni-based alloys, Cu, or Cu-based alloys may contain various trace components such as phosphorus (P) and / or sulfur (S) in an amount of less than 0.1 mass %. In addition, the internal electrode layer 3 may also be formed using a commercially available electrode paste. The thickness of the internal electrode layer 3 may be appropriately determined according to the intended use, etc.

[0034] < External electrodes >

[0035] The conductive material included in the external electrode 4 is not particularly limited. For example, a known conductive material such as nickel (Ni), copper (Cu), tin (Sn), Ag, Pd, Pt, gold (Au) or an alloy thereof, or a conductive resin may be used. The thickness of the external electrode 4 may be appropriately determined according to the application, etc.

[0036] < Dielectric composition >

[0037] The dielectric composition constituting the dielectric layer 2 of the present embodiment contains strontium (Sr) and tantalum (Ta) as main components. The dielectric composition of the present embodiment preferably further contains barium (Ba) as a main component.

[0038] The main component of the dielectric composition of this embodiment is {Ba x Sr (1-x)} m Ta4O 12 express.

[0039] x is preferably 0.75 or less, more preferably 0.1 to 0.75.

[0040] m is preferably 1.8 to 2.2, more preferably 1.9 to 2.1.

[0041] The crystal system of the main component crystal of the dielectric composition of the present embodiment is not particularly limited, but is preferably a tetragonal system or an orthorhombic system, and more preferably a tetragonal system.

[0042] The main component refers to a component that accounts for 80 to 100 parts by mole, preferably 90 to 100 parts by mole, based on 100 parts by mole of the element other than oxygen contained in the dielectric composition.

[0043] In addition, the dielectric composition of the present embodiment does not substantially contain titanium (Ti), niobium (Nb), alkali metals, and lead (Pb). “Does not substantially contain titanium, niobium, alkali metals, and lead” means that when the elements other than oxygen contained in the dielectric composition are set to 100 parts by mole, the total amount of “titanium, niobium, alkali metals, and lead” is 10 parts by mole or less, preferably 5 parts by mole or less.

[0044] The dielectric composition of the present embodiment may contain vanadium (V), aluminum (Al), magnesium (Mg), silicon (Si), calcium (Ca), manganese (Mn), chromium (Cr), rare earth elements, and the like as auxiliary components.

[0045] The density of the dielectric composition of this embodiment is preferably 5.72 g / cm 3 More preferably, 5.75 to 7.85 g / cm 3 In addition, the method for setting the density of the dielectric composition within the above range is not particularly limited, and examples thereof include a method of adjusting the sintering temperature of the dielectric composition, a method of adjusting the particle size of the calcined powder, or a method of adding a sintering aid, etc. In addition, in order to set the density within the above range, it is preferred that the sintering temperature be set to 1380 to 1600°C.

[0046] < Method for manufacturing multilayer ceramic capacitor >

[0047] Next, Figure 1An example of a method for manufacturing the multilayer ceramic capacitor 1 shown in FIG. 1 will be described.

[0048] In this embodiment, a calcined powder constituting the main component of the above-mentioned dielectric composition is prepared. The raw materials of each element constituting the main component are not particularly limited, and oxides of each element can be used. In addition, various compounds that can obtain oxides of each element by sintering can be used.

[0049] After the raw materials of the main component are weighed in a predetermined ratio, they are wet mixed for a predetermined time using a ball mill or the like. After the mixed powder is dried, it is heat treated in the air at a temperature of 700 to 1300° C. to obtain a calcined powder of the main component. In addition, the calcined powder is pulverized for a predetermined time using a ball mill or the like.

[0050] Next, a paste for making green chips is prepared. The obtained calcined powder of the main component and a solvent are kneaded to form a coating to prepare a paste for a dielectric layer. As the binder and the solvent, any known materials may be used.

[0051] The dielectric layer paste may contain additives such as a plasticizer and a dispersant as necessary.

[0052] The internal electrode layer paste is obtained by kneading the above-mentioned conductive material raw materials, a binder, and a solvent. The binder and the solvent may be known materials. The internal electrode layer paste may also contain a common material or additives such as a plasticizer as required.

[0053] The external electrode paste can be prepared in the same manner as the internal electrode layer paste.

[0054] Green sheets and internal electrode patterns were formed using the obtained pastes, and these were stacked to obtain green chips.

[0055] The obtained green chip is subjected to a binder removal treatment as necessary. The binder removal treatment conditions are preferably set at a holding temperature of 200 to 350°C, for example.

[0056] After the binder removal treatment, the green chip is sintered to obtain the element body 10. In this embodiment, the sintering atmosphere is not particularly limited and may be in air or in a reducing atmosphere. In this embodiment, the holding temperature during sintering is, for example, 1380 to 1600°C.

[0057] After sintering, the obtained element body 10 is subjected to reoxidation treatment (annealing) as necessary. For annealing conditions, for example, it is preferable to set the oxygen partial pressure during annealing to be higher than the oxygen partial pressure during sintering and to set the holding temperature to 1150° C. or less.

[0058] The dielectric composition constituting the dielectric layer 2 of the element body 10 obtained as described above is the above-mentioned dielectric composition. The element body 10 is subjected to end surface grinding, and an external electrode paste is applied and sintered to form the external electrode 4. Then, a coating layer is formed on the surface of the external electrode 4 by plating or the like as needed.

[0059] In this manner, the multilayer ceramic capacitor 1 of the present embodiment is manufactured.

[0060] According to the present embodiment, by including strontium and tantalum as main components, a dielectric composition having a constant and high relative dielectric constant in a wide temperature range can be obtained. Specifically, the dielectric composition according to the present embodiment can show a relative dielectric constant of 75 or more in a temperature range of -55 to 150°C, and a relative dielectric constant of 70 or more in a temperature range of -70 to 180°C.

[0061] In addition, according to the dielectric composition of this embodiment, in the temperature range of -55 to 150°C, the reference temperature can be set to 25°C and the capacity change rate can be set to within ±22%, so that the X8S characteristics can be satisfied. Furthermore, in the temperature range of -70 to 180°C, the reference temperature can be set to 25°C and the capacity change rate can be set to within ±22%.

[0062] Furthermore, according to the present embodiment, it is possible to obtain a dielectric composition that contains substantially no titanium, niobium, alkali metals, and lead and exhibits high density, high relative dielectric constant, low dielectric loss, and high resistivity.

[0063] The dielectric composition of the present embodiment contains tantalum and substantially does not contain niobium and titanium. On the other hand, the existing dielectric composition does not contain tantalum and contains niobium and titanium. The dielectric composition of the present embodiment has a tendency to show high resistivity and low dielectric loss compared to the existing dielectric composition. As a reason for this, it is believed that tantalum oxide (Ta2O5) is less likely to produce oxygen defects than niobium oxide (Nb2O5) and titanium oxide (TiO2).

[0064] Dielectric properties are properties based on the premise of being an insulator. Therefore, it is required that the dielectric composition has a high resistance so that the dielectric composition will not be semiconductorized or conductorized. Moreover, as mentioned above, tantalum oxide (Ta2O5) is less likely to produce oxygen defects than niobium oxide (Nb2O5) and titanium oxide (TiO2). In other words, the change of valence state is suppressed. Therefore, it is believed that the reduction of resistivity can be suppressed and high resistivity can be displayed in a wide temperature range. In addition, based on the same reason, it is believed that low dielectric loss can be displayed.

[0065] [ Second embodiment ]

[0066] < Film capacitors >

[0067] The schematic diagram of the film capacitor 11 of this embodiment is shown in Figure 2 Shown in. Figure 2 The thin film capacitor 11 shown has a lower electrode 112 and a dielectric film 113 formed in this order on a substrate 111 , and an upper electrode 114 is provided on the surface of the dielectric film 113 .

[0068] The material of the substrate 111 is not particularly limited, but the use of a Si single crystal substrate is excellent in terms of availability and cost efficiency as the substrate 111. When flexibility is important, Ni foil or Cu foil can also be used as the substrate.

[0069] The materials of the lower electrode 112 and the upper electrode 114 are not particularly limited as long as they function as electrodes. For example, Pt, Ag, Ni, etc. are mentioned. The thickness of the lower electrode 112 is not particularly limited, and is, for example, 0.01 to 10 μm. The thickness of the upper electrode 114 is also not particularly limited, and is, for example, 0.01 to 10 μm.

[0070] The composition and the crystal system of the main component of the dielectric composition constituting the dielectric thin film 113 of this embodiment are the same as those of the first embodiment.

[0071] The thickness of the dielectric thin film 113 is not particularly limited, but is preferably 10 nm to 1 μm.

[0072] < Method for manufacturing film capacitors >

[0073] Next, a method for manufacturing thin film capacitor 11 will be described.

[0074] There is no particular limitation on the film forming method of the thin film that eventually becomes the dielectric thin film 113. For example, vacuum evaporation method, sputtering method, PLD method (pulsed laser evaporation method), MO-CVD method (metal organic chemical vapor deposition method), MOD method (metal organic decomposition method), sol-gel method, CSD method (chemical solution deposition method), etc. are exemplified.

[0075] In addition, although the raw materials used in film formation may contain trace impurities or side components, there is no particular problem as long as the amount is not significantly detrimental to the performance of the film. In addition, the dielectric film 113 of this embodiment may also contain trace impurities or side components to the extent that the performance is not significantly detrimental.

[0076] In this embodiment, a film forming method using the PLD method will be described.

[0077] First, a Si single crystal substrate is prepared as the substrate 111. Next, SiO2, TiO x, Pt, and form the lower electrode 112 composed of Pt. The method of forming the lower electrode 112 is not particularly limited. For example, a sputtering method or a CVD method can be mentioned.

[0078] Next, the dielectric thin film 113 is formed by the PLD method on the lower electrode 112. In order to expose a portion of the lower electrode 112, a metal mask may be used to form a region where the thin film portion is not formed.

[0079] In the PLD method, first, a target material containing constituent elements of the target dielectric thin film 113 is placed in a film forming chamber. Then, a pulsed laser is irradiated on the surface of the target material. The surface of the target material is instantly evaporated by the strong energy of the pulsed laser. Then, the evaporated material is deposited on a substrate arranged in a manner opposite to the target material, and the dielectric thin film 113 is formed.

[0080] The type of target is not particularly limited, and alloys etc. can be used in addition to metal oxide sintered bodies containing constituent elements of the dielectric thin film 113 to be produced. In addition, in the target, each element is preferably evenly distributed, but the distribution may be uneven within a range that does not affect the quality of the dielectric thin film 113 obtained.

[0081] There is not necessarily one target, and a plurality of targets containing a part of the constituent elements of the dielectric thin film 113 may be prepared for film formation. The shape of the target is not limited, and may be a shape suitable for the film formation apparatus used.

[0082] In addition, in the case of the PLD method, in order to crystallize the dielectric thin film 113 to be formed, it is preferable to heat the substrate 111 with an infrared laser during film formation. The heating temperature of the substrate 111 varies depending on the constituent elements and composition of the dielectric thin film 113 and the substrate 111, but for example, the film is formed by heating to 600 to 800° C. By setting the temperature of the substrate 111 to an appropriate temperature, the dielectric thin film 113 is easily crystallized, and the occurrence of cracks generated during cooling can be prevented.

[0083] Finally, by forming the upper electrode 114 on the dielectric film 113, the thin film capacitor 11 can be manufactured. In addition, the material of the upper electrode 114 is not particularly limited, and Ag, Au, Cu, etc. can be used. In addition, the method for forming the upper electrode 114 is not particularly limited. For example, it can be formed by evaporation or sputtering.

[0084] As mentioned above, although embodiment of the present invention was described, it is needless to say that the present invention is not limited to the above embodiment at all, and can be implemented in various different modes within the scope not departing from the gist of the present invention.

[0085] In the above-mentioned embodiment, the electronic component of the present invention is described as a laminated ceramic capacitor or a film capacitor. However, the electronic component of the present invention is not limited to a laminated ceramic capacitor or a film capacitor, and may be any electronic component as long as it has the above-mentioned dielectric composition.

[0086] For example, a single-plate type ceramic capacitor may be provided in which a pair of electrodes are formed on a single-layer dielectric substrate made of the above-mentioned dielectric composition.

[0087] Furthermore, the electronic component of the present invention may be a filter, a duplexer, a resonator, a vibrator, an antenna, or the like, in addition to a capacitor.

[0088] Example

[0089] Hereinafter, the present invention will be described in more detail using examples and comparative examples. However, the present invention is not limited to the following examples.

[0090] [ Experiment 1 ]

[0091] < Sample No. 1 to 5 >

[0092] In Sample Nos. 1 to 5, starting materials for dielectric compositions were prepared to give the components shown in Table 1 by sintering. The prepared starting materials (powders) were weighed so that the metal element ratios of the composition formula shown in Table 1 were obtained.

[0093] Next, the weighed powders were wet mixed using ion exchange water as a dispersion medium by a ball mill, and the mixture was dried to obtain a mixed raw material powder. The obtained mixed raw material powder was then heat treated in the atmosphere at a temperature of 900° C. for 2 hours to obtain a calcined powder of the main component.

[0094] The obtained calcined powder of the main component was wet-pulverized by a ball mill using ion-exchanged water as a dispersion medium, and then dried to obtain a dielectric raw material.

[0095] To 100 parts by mass of the obtained dielectric raw material, 10 parts by mass of an aqueous solution containing 6 parts by mass of a polyvinyl alcohol resin as a binder was added, and granulation was performed to obtain granulated powder.

[0096] The obtained granulated powder was put into The mold is 0.6 ton / cm 2 The pre-punching is performed at a pressure of 1.2 ton / cm 2 The main stamping is carried out with a pressure of to obtain a disc-shaped forming body.

[0097] Next, the obtained molded body was subjected to a binder removal treatment, sintering and annealing under the following conditions to obtain a device body.

[0098] The binder removal treatment conditions were as follows: holding temperature: 400° C., temperature holding time: 2 hours, and atmosphere: in air.

[0099] The sintering conditions were as follows: holding temperature: 1425-1500°C, temperature holding time: 2 hours, atmosphere: humidified N2+H2 mixed gas (oxygen partial pressure: 10 -12 MPa). In addition, a wetting agent is used to humidify the atmosphere gas during sintering.

[0100] The annealing conditions were as follows: holding temperature: 1050°C, temperature holding time: 2 hours, atmosphere gas: humidified N2 gas (oxygen partial pressure: 10 -7 MPa). In addition, a wetting agent is used to humidify the atmosphere gas during annealing.

[0101] The relative dielectric constant, dielectric loss (tan δ), density, resistivity and crystal system of the obtained sintered body (dielectric composition) were investigated by the following method. In addition, in order to measure the relative dielectric constant, dielectric loss and resistivity, an In-Ga electrode was applied to the above-mentioned dielectric composition (sintered body) to obtain a disc-shaped ceramic capacitor sample (capacitor sample).

[0102] < Relative dielectric constant and dielectric loss (tanδ) >

[0103] At room temperature (20°C), a digital LCR meter (4284A manufactured by YHP) was used to input a signal with a frequency of 1kHz and an input signal level (measurement voltage) of 1Vrms to the capacitor sample to measure the capacitance C and tanδ. Then, the relative dielectric constant was calculated based on the thickness of the sintered body, the effective electrode area, and the capacitance C obtained by the measurement. The results are shown in Table 1.

[0104] In addition, the relative dielectric constant was measured every 10°C in the temperature range of -70 to 180°C. Figure 3 Shown in.

[0105] < density >

[0106] The density of the dielectric composition was measured as follows. First, the volume V of the dielectric composition was calculated. Next, the mass m of the disc-shaped dielectric composition was measured, and m / V was calculated to obtain the density of the dielectric composition. The results are shown in Table 1.

[0107] < Resistivity >

[0108] The insulation resistance of the capacitor sample was measured at a reference temperature (25° C.) using a digital resistance meter (R8340 manufactured by ADVANTEST). The resistivity was calculated from the obtained insulation resistance, effective electrode area, and thickness of the dielectric composition. The results are shown in Table 1.

[0109]

Table 1

[0110]

[0111] Sample numbers 1 to 5 are oxides belonging to the polar point group. Figure 3 Sample No. 1 containing barium, strontium and tantalum as main components has a relative dielectric constant of more than 100 in a wide measurement temperature range (-70 to 180°C), and has a higher relative dielectric constant than other oxides (sample Nos. 2 to 5).

[0112] In addition, if Figure 3 As shown, in the temperature range of -55 to 150°C, the capacity change rate of sample No. 1 is within ±22% when the reference temperature is set to 25°C, so it can meet the X8S characteristics. Furthermore, in the temperature range of -70 to 180°C, the capacity change rate is within ±22% when the reference temperature is set to 25°C.

[0113] From Table 1, it can be confirmed that Sample No. 1 containing barium, strontium, and tantalum as main components has a higher density, a higher relative dielectric constant, a lower dielectric loss, and a higher resistivity than other oxides (Sample Nos. 2 to 5).

[0114] [ Experiment 2 ]

[0115] < Sample No. 21-26, 31-34 >

[0116] In sample numbers 21 to 26 and 31 to 34, the composition and addition amount of the starting raw materials of the dielectric composition are as follows, and the sintering holding temperature is set to 1550°C. In addition, the dielectric composition is obtained in the same manner as in Experiment 1, and the density, relative dielectric constant, dielectric loss and resistivity are investigated. In addition, the crystal system is investigated by the following method. The results are shown in Tables 2 and 3. In addition, in sample numbers 21 to 26 and 31 to 34, it can be confirmed that in any case, in the temperature range of -70 to 180°C, the relative dielectric constant is 70 or more.

[0117] That is, in Experiment 2, powders of barium carbonate (BaCO3), strontium carbonate (SrCO3) and tantalum oxide (Ta2O5) were prepared as starting materials of the dielectric composition. x Sr (1-x)} m Ta4O 12The starting materials prepared were weighed in the manner indicated in Table 2 or Table 3 to give the compositions.

[0118] < Crystal system >

[0119] The obtained dielectric composition was subjected to electron beam diffraction, and the crystal system was analyzed by analyzing the electron beam diffraction pattern.

[0120]

Table 2

[0121]

[0122]

Table 3

[0123]

[0124] From Tables 2 and 3, it can be confirmed that the relative dielectric constants of sample No. 26 containing strontium and tantalum as main components and sample Nos. 21 to 25 and 31 to 34 containing barium, strontium, and tantalum as main components are high.

[0125] From Table 2, it can be confirmed that when x is 0.75 or less (sample numbers 22 to 26), the samples exhibit higher density, higher relative dielectric constant, lower dielectric loss, and higher resistivity than when x is 0.80 (sample number 21).

[0126] From Table 2, it can be confirmed that when x is 0.10 to 0.75 (sample numbers 22 to 25), a higher relative dielectric constant is shown than when x is 0.80 (sample number 21) or when x is 0.00 (sample number 26).

[0127] It can be confirmed from Table 3 that when m is 1.9 to 2.1 (sample numbers 32, 24, and 33), compared with when m is 1.8 (sample number 31) or 2.2 (sample number 34), higher density, higher relative dielectric constant, lower dielectric loss, and higher resistivity are exhibited.

[0128] [ Experiment 3 ]

[0129] < Sample No. 41~45 >

[0130] In sample numbers 41 to 45, the density, relative dielectric constant, dielectric loss and resistivity of the dielectric composition (sintered body) were measured in the same manner as sample number 1 except that the sintering temperature was changed in the range of 1375 to 1500°C in each sample. The results are shown in Tables 4 and Figures 4 to 6 Shown in.

[0131]

Table 4

[0132]

[0133] From Table 4 and Figures 4 to 6 It was confirmed that when the density exceeded 5.74 (sample numbers 1, 42 to 45), the dielectric loss and the resistivity were lower than when the density was 5.74 (sample number 41).

[0134] Explanation of symbols

[0135] 1...Multilayer ceramic capacitor

[0136] 10……Component body

[0137] 2…Dielectric layer

[0138] 3...Internal electrode layer

[0139] 4...External electrodes

[0140] 11……Film capacitors

[0141] 111...Substrate

[0142] 112...Lower electrode

[0143] 113...Polycrystalline dielectric thin film

[0144] 114...Upper electrode

Claims

1. A dielectric composition, wherein: Its main components are {Ba x Sr (1-x) } m Ta4O 12 express, x is 0.1 to 0.75, m is 1.9~2.

1.

2. The dielectric composition according to claim 1, wherein x is 0.25 to 0.

50.

3. The dielectric composition according to claim 1, wherein The crystal system of the main component crystal is tetragonal system.

4. An electronic component, wherein: A dielectric composition according to any one of claims 1 to 3.